Formation of Adsorbable Organic Bromine in Treated Drinking Waters - Langsa, Markus Heryanto (Curtin University, 2016)
Chlorination of drinking waters containing naturally occurring bromide and natural organic matter leads to formation of disinfection by-products, including brominated organic compounds which are of potential public health concern. Adsorbable organic halogen is the only method available to measure all halogenated organic disinfection by-products in drinking waters. This Thesis describes detailed mechanistic studies on the formation of adsorbable organic bromine, which will aid in minimisation of the production of these by-products during drinking water disinfection.